Wound healing properties of biotransformed asiaticoside by aspergillus niger - Omar, Muhammad Nor; Alfarra, Helmi Yousi; Ichwan, Solachuddin Jauhari Arief (Penerbit UMT, 2017)
Biotransformation is extensively used to create useful metabolites from various natural products and as an alternative to chemical synthesis for the preparation of pharmacologically-active compounds. This study investigated the effects of asiaticoside and its biotransformed product on wound healing activities. Asiaticoside, the bioactive constituent of Centella asiatica has been reported to possess wound healing properties. Microbial transformation of asiaticoside using Aspergillus niger was carried out to produce an asiaticoside biotransformed product and the wound healing activities of asiaticoside and its biotransformed product were investigated. Their effects on transforming growth factor-beta 1 (TGFβ1) and tissue inhibitor of metalloproteinase 1 (TIMP1) gene expression were examined to understand the mode of action and on the cell proliferation and wound healing using human keratinocytes. Results of in vitro study showed that asiaticoside concentrations between 7.5 and 120 μg/mL gave higher value of cell proliferation than the negative control. On the other hand, the biotransformed product concentrations between 0.058 and 3.75 μg/mL exhibited high cell viability but the viability was lowest at 15.0 μg/mL, suggesting cytotoxic effects on the cells. In wound healing assays, there were significant differences on wound closure in comparison to the negative control (P<0.05). Both asiaticoside and the biotransformed product increased the expression of TGFβ1 and TIMP1 respectively, with the latter showing more enhanced expressions of both genes. The biotransformed product also showed faster migration and healing rate under microscopic observation.